Learning from rivals: the memory-inconsistent strategy. Issue 5 (27th May 2021) - Jiang, Chuandi; Muldoon, Jeffrey; Alhorr, Hadi
Abstract : Purpose: The purpose of this paper is to examine the role of competitive memory that assists the new ventures to overcome challenges due to the liability of newness in the strategic adaptation stage. Design/methodology/approach: This is a conceptual paper. Through a critical literature review on new venture survival and organizational memory, the authors identified the possibility for new ventures to learn from other firms from organizational learning and resource-based perspectives. Findings: The authors found that new ventures can acquire and analyze the existing rivals' strategic moves documented in multiple sources, such as published yearbook, financial report, media, etc., and develop their own strategies. New ventures can also benefit from the relatively high degree of organizational inertia of existing rivals. Practical implications: New venture survival and performance are substantially affected by the initial organizational learning and strategic decision-making. Applying the memory-inconsistent strategy (MIS), new ventures that lack competitive experiences can learn from their rivals by internalizing the rivals' competitive memory as strategic resources and utilizing such resources to develop a competitive strategy. Originality/value: New venture research in competitive markets focuses on the challenges and difficulties due to the lack of experiences, neglecting the fact that new ventures can learn from competitive memories of existing rivals. However, the lack of competitive experiences also means a lower degree of organizational inertia and other strategic commitments. The authors introduce the MIS and suggest that new ventures can benefit from strategic flexibility and create a temporary competitive advantage by surprising existing firms.